Radiopharmacy and nuclear medicine: advancing precision in modern healthcare - Othman, Muhamad Faiz (Faculty of Pharmacy, 2025)
Nuclear medicine stands at the vanguard of precision healthcare, driven by rapid advancements in radiopharmaceutical science. Once centered on a handful of diagnostic isotopes (Technetium-99m and Iodine-131), the field now embraces a wide array of targeted radiopharmaceuticals designed not only to image but also to treat complex diseases with molecular-level specificity.